SUICIDE AND ABSURD LIFE IN THE MYTH OF SISYPHUS BY CAMUS - Aseel Abbas Khudhair (Journal of Learning on History and Social Sciences, 2024)
The subject of research into suicide constitutes a fundamental link in the topics of the humanities and social sciences, in addition to the fact that the permanent and inherent obsession in humans is death, and thus this proposition imposes itself in the contemporary period as it coincides with the global crises that threaten human existence. In addition to learning about the ideas of Albert Camus and identifying the factors that produced this absurd thought. The research concluded important results, as there is no meaning behind life, unless a meaning is determined for it. One must accept the absurd instead of rejecting it in order to be able to live in peace. . So one must imagine the happy Sisyphus that Albert mentioned in his work. Suicide is not an easy matter, and the matter should be taken seriously because human existence creates life and not the other way around